Treatment of Chronic Patellar Tendon Rupture with Hamstrings Tendon Autograft - Valianatos, Panagiotis; Papadakou, Evgenia; Erginoussakis, Dimitrios; Kampras, Dimitrios; Schizas, Nikitas; Kouzoupis, Anastasios (The Journal of Knee Surgery, 2020)
We describe a new simple reconstruction for neglected chronic ruptures of patellar tendon using ipsilateral hamstrings tendon autograft. This has been validated in thirteen patients with mean follow up six years resulting in favorable outcome. Thirteen patients with mean age 58.2 years (range 30–64 years) presented with chronic patellar tendon rupture. They all underwent patellar tendon reconstruction using ipsilateral hamstrings tendon autograft. The average time from injury was 10 months (range 3–20 months). The cause of rupture was fall from height or after TKA and the preoperative Lysholm score was 65 (range 50–80). Postoperatively with a mean follow up of six years (range 5–7 years), all patients had a stable knee with mean flexion of 123°, extension lag 0°, and Insall-Salvati index 1.2. Quadriceps power was regained in 8 cases to 5/5 and in 5 cases to 4/5. No complications were inspected. The postoperative Lysholm score was 93 (range 89–95). Patellar tendon reconstruction using ipsilateral hamstrings as free autograft, consists an effective treatment option for chronic neglected patellar tendon ruptures. Our technique has favorable clinical outcome, complications are not expected, and consist a simple and anatomic reconstruction with a powerful graft, without the requirement for allograft or implants.
Keywords: patellar tendon; autograft; total knee arthroplasty